KOMPARASI MODEL PEMBELAJARAN INKUIRI TERBIMBING DENGAN INKUIRI BEBAS TERHADAP KETERAMPILAN PROSES SAINS SISWA PADA MATERI HUKUM KEKEKALAN MASSA KELAS X MIPA SMA NEGERI 1 PONTIANAK - Daniel Erikko; Mahwar Qurbaniah; Tuti Kurniati (Jurnal Ilmiah Ar-Razi, 2018)
This research aimed to know students’ comparison between the process skills of science using controlled inquiry and free inquiry learning X grade at MIPA SMA Negeri 1 Pontianak. This research was based on the importance of the students’ skill in the learning process of the scientific chemical to encourage students to be active in the learning process. Using quasy experimental method of nonquivalent control group design. Data collection techniques used were observation and measurement techniques. The data collecting tools were measurement and direct observation. The data analysis used were non-parametical statistic using U-Mann Whitney test and the value of the Gain. The analysis value of science process skill test class between controlled inquiry and free inquiry using U-Mann Whitney test was obtained p value (0.004 < 0.05), means there was the difference between the process skill science students’ taught with the model of controlled inquiry and the model of free inquiry. The gain value used was to find out the most effective learning model. The analysis of gain value using free inquiry (0.79 with high category) was higher than using controlled inquiry (0.69 with medium categories). It showed that the model of free inquiry more effective than controlled inquiry model to improve the process skill of science on mass constancy material X grade at MIPA SMAN 1 Pontianak.Keywords: The process skill of science, Comparison, Controlled inquiry, Free inquiry, Law of mass constancy